Making grown-up oil palm gardens more remunerative - Ramachandrudu, K; Arulraj, S; Rao, B N; Suneetha, V (Indian Horticulture, 2019)
The shade-loving and shade tolerant crops may be chosen in bearing oil palm gardens. However, success of intercropping in oil palm depends on the selection of suitable crops and efficient management.